DETERMINATION OF TIN IN ENVIRONMENTAL SAMPLES BY ATOMIC FLUORESCENCE SPECTROMETRY - Garcez, Daniel L. [UNESP]; Menegario, Amauri A. [UNESP]; Ferreira, Jose R.; Corns, Warren T.; Suarez, Carlos A. [UNESP]; Rolisola, Ana M. C. M. [UNESP]; Yabuki, Lauren N. M. [UNESP] (Soc Brasileira Quimica, 2016)
DETERMINATION OF TIN IN ENVIRONMENTAL SAMPLES BY ATOMIC FLUORESCENCE SPECTROMETRY. An analytical method to determine tin concentrations in natural samples, by coupling atomic fluorescence spectrometry, hydride generation and flow injection system was developed. The sample digestion procedure and the conditions of hydride generation were fully optimized. The best conditions for the generation of SnH4 were obtained with NaBH4 4% (m v(-1)) and HCl 0.6 mol L-1. The optimized flow rates were 1.2 mL min(-1) for sample, 1.2 mL min(-1) for HCl and 1.6 mL min(-1) for NaBH4 solution. The sample volume was 500 mu L. The best acid volume for digestion of solid samples was stablished to be 3 mL HNO3 + 1 mL HCl. The accuracy of the method was established by the analysis of certified reference materials and by comparative determinations, using inductively coupled optical emission spectrometry. The approach developed was shown to offer a robust method with excellent accuracy and precision for the determination of Sn in environmental samples. Finally, the method was applied to analyse the soil, sediment and water samples, collected in area under anthropogenic activities: processing area of cassiterite in Corumbatai/SP. The obtained data indicated that there was alteration in the natural quality of the environment as a result of the activities developed in that site.
Keywords: tin; AFS; HG; FI; environmental samples